2021
DOI: 10.1542/peds.2020-009142
|View full text |Cite
|
Sign up to set email alerts
|

Empiric Vancomycin Reduction in a Pediatric Intensive Care Unit

Abstract: BACKGROUND At our institution, empirical vancomycin is overused in children with suspected bacterial community-acquired infections (CAIs) admitted to the PICU because of high community rates of methicillin-resistant Staphylococcus aureus (MRSA). Our goal was to reduce unnecessary vancomycin use for CAIs in the PICU. METHODS Empirical PICU vancomycin indications for suspected CAIs were developed by using epidemiological risk f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Vancomycin was mainly prescribed empirically, with only 4.1% of all admissions receiving culture‐guided vancomycin treatment. This practice was reported in both adult and paediatric wards, in developed countries such as the United States and developing countries such as Iran 6,20,21 . For instance, Keyserling et al 22 reported that 84% of vancomycin prescription in neonatology wards is empiric.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Vancomycin was mainly prescribed empirically, with only 4.1% of all admissions receiving culture‐guided vancomycin treatment. This practice was reported in both adult and paediatric wards, in developed countries such as the United States and developing countries such as Iran 6,20,21 . For instance, Keyserling et al 22 reported that 84% of vancomycin prescription in neonatology wards is empiric.…”
Section: Discussionmentioning
confidence: 97%
“…This practice was reported in both adult and paediatric wards, in developed countries such as the United States and developing countries such as Iran. 6,20,21 For instance, Keyserling et al 22 reported that 84% of vancomycin prescription in neonatology wards is empiric. The high empiric use of vancomycin at JUH is alarming.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the identification of MRSA among only one in eight patients, vancomycin was used in over three-quarters of all patients. Excessive empiric use of vancomycin contributes to resistance, with minimum inhibitory concentration (MIC) “creep” widely reported in the literature [ 28 , 29 , 30 , 31 ]. The ability for rapid pathogen identification may preclude the prescription of irrelevant antibiotics, thereby removing the need to consider de-escalation in some cases.…”
Section: Discussionmentioning
confidence: 99%